(3GbJQGfGJ GdchGcH aj GdHQhL GdGKfi YTQ heG jdMb HPdcs - (3LYaQ Hf eMeO Hf YeQ GdHdNj, CHh eYTQ , nCoHh nerYnTQ Gdnandcj,J (B272 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg GYde Cf Mce GbJQGfGJ gPg GdchGcH LGQjg McegG Ydi GdHdOGf GdJi JMJ adc GdHQhL GdJi gi GKfG YTQ HQLkG s
(3BNQgG (B:s
(3YfO GdbWY hEPG CTQa Ydi GdQGUO Od Ydi bJd GdCTQa hPhi GdhLhg s
(3Gdajde ZjQ ehLhOs
(3ebWY HYO GdhQbI GdSGHYI hGdKdGKjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B148s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B395 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B11 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs